Reflections on the Relations between Archival Science and Knowledge Organization: A Focus on Archival Classification - Veronez, Wilson Roberto [UNESP]; Troitiño, Sonia [UNESP]; Martínez-Ávila, Daniel; San Segundo, Rosa (Nomos Verlag, 2024)
This paper aims to discuss some preliminary notes on the interdisciplinary relations between Archival Science and Knowledge Organization. It is based on the assumption that the studies on the intersection between the two fields would benefit from more critical analyses, with more in-depth theoretical and applied discussions, as well as the development of new foundations and guidelines. In the field of Archival Science, studies on its epistemological character exist in the literature, although scarce, and thus, in order to establish a relationship with Knowledge Organization, we propose the analysis of archival classification as the fundamental process that connects both fields. As a conclusion, we consider that these two fields are related although with a certain level of incipience of epistemological studies and a lack of more in-depth reflection on other topics related to Archival Science such as description, archival diplomatics, document identification, document evaluation as well as the classification scheme and the records schedule.